1988
DOI: 10.2307/1943164
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Correlates of Breeding‐Site Fidelity in Bobolinks (Dolichonyx Oryzivorus)

Abstract: To investigate the relationship between reproductive success (RS) and breeding—site fidelity in a transequatorial migrant, we studied two populations of marked Bobolinks (Dolichonyx oryzivorus) in upstate New York during 1982—1985. At these sites, 44% of the males and 25% of the females resident in one year returned in one or more subsequent years. There were more nests built, eggs laid, eggs hatched, and young fledged in territories of returning males in this polygynous species than in territories of males th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(67 citation statements)
references
References 20 publications
(24 reference statements)
4
62
0
Order By: Relevance
“…It is hypothesized that the reuse of nesting site is related to previous successful nesting attempts in the same site, a behavior that would be favored by natural selection (Blancher and Robertson, 1985;Gavin and Bollinger, 1988;Gauthier, 1990), and is supported by empirical evidence (Harvey et al, 1979;Hepp andKennamer, 1992, Thorstrom et al, 2001;Styrsky, 2005). In our study, however, reuse of nest sites was not related to the fate of previous nesting attempts at that site.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…It is hypothesized that the reuse of nesting site is related to previous successful nesting attempts in the same site, a behavior that would be favored by natural selection (Blancher and Robertson, 1985;Gavin and Bollinger, 1988;Gauthier, 1990), and is supported by empirical evidence (Harvey et al, 1979;Hepp andKennamer, 1992, Thorstrom et al, 2001;Styrsky, 2005). In our study, however, reuse of nest sites was not related to the fate of previous nesting attempts at that site.…”
Section: Discussionsupporting
confidence: 61%
“…This is contrary to the positive association between the reuse of nesting sites and the success of the previous breeding attempt described for various other species (Harvey et al, 1979;Blancher and Robertson, 1985;Gavin and Bollinger, 1988;Gauthier, 1990;Hepp and Kennamer, 1992). Alternative explanations for this lack of relationship may include scarcity or high overall quality of available nesting sites.…”
Section: Discussionmentioning
confidence: 61%
“…Previous reproductive success has frequently been shown to influence the breeding dispersal decisions of many birds (Gavin and Bollinger 1988, Bollinger and Gavin 1989, Haas 1998, Hoover 2003. We demonstrated that female breeding territory fidelity was sensitive to prior reproductive success.…”
Section: Reproductive Success and Breeding Territory Fidelitymentioning
confidence: 61%
“…The likelihood of high competition in males, as well as the higher mortality in females, seems to be an important factor affecting both territory settlement in the year of ringing and fidelity probability in subsequent years. On the other hand, in a few bird species reproductive outcome did not affect the likelihood of return in successive years (Gavin & Bollinger 1988, Haig & Oring 1988, Payne & Payne 1993, Pyle et al 2001, Shutler & Clark 2003, Hallworth et al 2008.…”
Section: Discussionmentioning
confidence: 99%